Generator noise as a factor influencing the environment and human health (on the example of Kremenchuk) - Alekseeva, T. M. (Man and Environment. Issues of Neoecology, 2026)
Purpose. To investigate the impact of operating generators on the ecological conditions of the urban environment and public health, using the central part of Kremenchuk as a case study, with a view to reducing this impact. Methods: analysis, synthesis, comparison, questioning method, statistical method, cartographic method. Results. Low-power generators are mainly installed in the central part of Kremenchuk: petrol generators, which are not equipped with protective enclosures, diesel models of the same power rating without protective enclosures, low-power petrol generators without enclosures, inverter models, petrol generators of different power rating, equipped with protective enclosures. There are zones with a high concentration of generators in the centre of Kremenchuk, where the noise level does not comply with health standards; this is unacceptable as the area features by residential developments and numerous educational, medical and recreational facilities. Generators are installed at the distance of 1 to 2-3 metres from a pedestrian zone and this has a negative impact on the local population. The distance between them is negligible, so their areas of influence overlap. A study of the impact of generator noise on the quality of human sleep showed that it constantly or often interferes with a full night’s rest. A study of the impact of generator noise on the ability to concentrate showed that there were constant problems with concentration at work. Generator noise causes a person to be irritable and creates a feeling of discomfort. Conclusions. Inverter generators and other models equipped with protective enclosures for reducing the negative noise impact on the town environment and the population health are recommended for installation. Optimal places for their location shall be selected, sound isolation shall be improved, and a legal reasoning for a generator exploitation for the town residents’ interest’s protection shall be established.